Better Natural Ventilation Design for Single Sided Apartments Utilising Computational Fluid Dynamics - Neihad H. Al-Khalidy (International Journal of Architectural Engineering Technology, 2020)
Wind-driven natural cross ventilation to many single-aspect apartments can be achieved via building indentations and façade articulation. The ventilation rate of these apartments will rely on pressures differences between openings caused by approaching wind pressure, local wind climate and interaction with the surrounding built environment and external pressure gradients on the building indentations or any other facades articulation and their potential driving force on natural ventilation. Detailed simulation methods are therefore required to consider all above mentioned parameters and provide internal and external airflow information to the design team to allow for design modifications or refinement where required to provide robust natural cross ventilation for such apartments. This study assesses the above parameters for a proposed development, designed with recesses and slots to enhance natural cross ventilation in single-sided apartments, and presents a reliable procedure to advise on compliance with national and/or international design guidelines utilising an advanced combined outdoor-indoor Computational Fluid Flow (CFD) analysis integrated with localized weather data for the project site.